Analysing ceramic design semantic representation through product gestalt - Mohamed Raif, Diana (2025)
Design thinking is a way to improve the world by combining aesthetics, ethics, and knowledge. Designers often struggle to explain how they form the connections that lead to desired outcomes and why these judgments are sensible, as the reasoning behind design choices can be elusive. Furthermore, existing literature on design cognition suggests that novice designers frequently struggle to clarify the abstract concepts they consider or how their intentions align with their physical actions in generating, selecting, and refining ideas. As Norman Theory highlights, designers must navigate both explicit and implicit signals to create user-friendly objects that require no instructional manuals and reduce the likelihood of user confusion. Additionally, it emphasizes that sketching and model-making are crucial for idea generation. This study identifies and characterizes the semantic representation of design in relation to form creation, while exploring the affordance-based design approach that proves useful in innovative product development within critical design situations. It examines the design thinking process and its application to product gestalt within the industrial ceramic design context. This research seeks to establish an innovation strategy for capturing the thinking process and protocol of ceramic designers, specifically in critical design scenarios. The data collection process is divided into three phases: the first involves a literature review, the second includes data gathering through surveys and interviews, and the third focuses on experiments based on video observations. This study evaluates product form design from the perspective of Product Gestalt theory, linking related design fields and product design to form creation. Product form design, as an innovative technique in industry, requires significant visual discernment, making it essential to have a reliable decision support system for designers. Ultimately, the study identifies the semantic representation of design in form creation, describes the affordance-based design approach, and empirically explores the designer's approach to understanding product gestalt in industrial ceramic design processes.